2019
DOI: 10.1002/pchj.317
|View full text |Cite
|
Sign up to set email alerts
|

Involuntary mental time travel in individuals with schizotypal personality features

Abstract: Involuntary mental time travel (MTT) refers to the phenomenon of mentally reliving past experiences or pre-living possible future events in an involuntary form. Few studies have explored involuntary MTT in individuals with schizotypal personality features. The present study aimed to first explore the psychometric properties of the Involuntary Autobiographic Memory Inventory (IAMI) in a Chinese sample (Study 1), and then to explore whether individuals with schizotypal personality features experience involuntary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Recent studies in individuals with high schizotypal traits also showed that they were more likely to engage in mind wandering (Kane et al, 2016; Yamaoka & Yukawa, 2020). In addition, positive schizotypal traits were positively associated with frequency of involuntary mental time travel, which shares similarities with mind wandering; for example, both were task‐unrelated thoughts (T. Chen et al, 2020). Therefore, we hypothesized that mind wandering would play a mediating role in the relationship between schizotypal traits and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies in individuals with high schizotypal traits also showed that they were more likely to engage in mind wandering (Kane et al, 2016; Yamaoka & Yukawa, 2020). In addition, positive schizotypal traits were positively associated with frequency of involuntary mental time travel, which shares similarities with mind wandering; for example, both were task‐unrelated thoughts (T. Chen et al, 2020). Therefore, we hypothesized that mind wandering would play a mediating role in the relationship between schizotypal traits and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Schizotypal traits exist widely in healthy people, high-risk groups of schizophrenia, and patients with schizophrenia with different severity (Nelson et al, 2013;Wang et al, 2012). Schizotypal traits have received a considerable amount of research attention in recent years (T. Chen et al, 2020;Cohen et al, 2018;Debbané & Mohr, 2015;Muller et al, 2021;R. Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above‐mentioned studies are related to voluntary MTT (i.e., participants were required to recall or imagine events related to cues), but several studies have also examined involuntary MTT (i.e., memories of personal events or imagined future events that come to mind spontaneously) along the SCZ spectrum. For example, individuals with high psychotic‐like experiences or high levels of schizotypy reported a higher frequency of involuntary MTT (Allé et al, 2019; Chen et al, 2020; Jones & Steel, 2012), a higher vividness and sense of reliving (Allé et al, 2019; Marks et al, 2012), and a more negative mood (Allé et al, 2019; Chen et al, 2020) than controls. In view of the inconsistent findings, more studies are needed to clarify MTT performance in individuals with a high level of schizotypy.…”
Section: Introductionmentioning
confidence: 99%